The compressive response of ultra-high molecular weight polyethylene fibres and composites. (1st October 2015) - Attwood, J.P.; Fleck, N.A.; Wadley, H.N.G.; Deshpande, V.S.
Abstract: Measurements are reported for the compressive response of ultra-high molecular weight polyethylene (UHMWPE) fibres and laminated composites loaded along the fibre direction. The compressive strength of the fibres was measured by both recoil tests and knot (or bend) tests. The strength of the fibres is governed by micro-kinking of the fibrils within the fibres. The recoil tests suggest that this kinking occurs at a compressive stress of approximately 340 MPa. Consistent with observations of other fibres such as Kevlar and carbon fibres, the compressive strength inferred from bending tests is approximately a factor of two higher than that from a direct compression test, such as the recoil test. The in-plane compressive response of laminated UHMWPE composites was measured using notched specimens. Two grades of composites with shear strengths of about 1.5 and 0.5 MPa were investigated and found to have compressive strengths of about 12 MPa and 3 MPa, respectively. Thus, unlike Kevlar composites, the composite compressive strength is not governed by the compressive strength of the fibres but by the micro-buckling of the composite plies. Detailed experimental measurements are reported for the kink-band width, fibre rotation within the band and its subsequent broadening after lock-up due to fibre rotation. These are shown to be adequately modelled by traditional kinking theory while a net section stress analysis models the propagation of the micro-buckle with sufficient fidelity.